2023
DOI: 10.3390/ijerph20196901
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Balwierz et al. Potential Carcinogens in Makeup Cosmetics. Int. J. Environ. Res. Public Health 2023, 20, 4780

Ishrat Chaudhuri,
Yufanyi Ngiewih,
Len Levy
et al.

Abstract: We read with interest the article by Balwierz et al. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This risk would not exist if IARC classified carbon black as Class 3. It is important to note that there is "inadequate evidence in humans" regarding the carcinogenicity of carbon black, which aligns with the viewpoint of Chaudhuri et al [1]. It should be noted that the studies referenced as 112 [3] and 78 [4] by us, as confirmed by Chaudhuri, do not specifically address the risk associated with the lungs.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…This risk would not exist if IARC classified carbon black as Class 3. It is important to note that there is "inadequate evidence in humans" regarding the carcinogenicity of carbon black, which aligns with the viewpoint of Chaudhuri et al [1]. It should be noted that the studies referenced as 112 [3] and 78 [4] by us, as confirmed by Chaudhuri, do not specifically address the risk associated with the lungs.…”
mentioning
confidence: 67%
“…Comments by Chaudhuri et al (2023) [1] raise several helpful points concerning the terminology utilized in the preparation of our paper and provide valuable additional data to support our publication. The viewpoint expressed by Chaudhuri et al offers an opportunity to enhance and broaden the discussion in our article, which primarily aimed to shed light on the somewhat ambiguous and non-obvious issue of the presence of potentially carcinogenic substances in cosmetics.…”
mentioning
confidence: 81%